Loss Of Future Earnings, Loss Of Earning Capacity And The Civil Law (Amendment) Act, 1984 - BALAN, P (Journal of Malaysian and Comparative Law, 1990)
Loss Of Future Earnings, Loss Of Earning Capacity And The Civil Law (Amendment) Act, 1984